30 Gy single dose stereotactic body radiation therapy (SBRT): Report on outcome in a large series of patients with lung oligometastatic disease. (August 2018) - Osti, M.F.; Agolli, L.; Valeriani, M.; Reverberi, C.; Bracci, S.; Marinelli, L.; De Sanctis, V.; Cortesi, E.; Martelli, M.; De Dominicis, C.; Minniti, G.; Nicosia, L.
Highlights: SBRT is a safe and effective treatment option for lung metastases. The optimal dose and fractionation are still unknown. 166 lung lesions in 129 patients were treated with 30 Gy single dose SBRT. Long LPFS especially for small lesions, and tolerable severe toxicity are reported. After a long-term follow-up 30 Gy single dose SBRT is effective and well tolerated. Abstract: Objectives: To evaluate the local control (LC) and long term adverse effects in a series of patients with lung metastases who received 30 Gy in single dose with stereotactic technique. Materials and Methods: Between December 2008 and April 2016, a total of 166 lung metastases in 129 patients affected by oligometastatic disease were treated at our Institution with stereotactic body radiotherapy (SBRT). Mainly, the primary tumors were non small-cell lung cancer and colorectal cancer (45.2% and 28.8%, respectively). Prognostic factors were also assessed. Results: The median follow-up was 38 months. Local progression occurred in 24 (14.4%) lesions in 21 patients. Intra-thoracic progression (new lung lesions or thoracic lymph node metastases) occurred in 59 (45.7%) patients. Forty-five (34.8%) patients had distant progression after a median time of 14 months. The 3- and 5-years local relapse-free survival (LPFS) were 80.1% and 79.2% (median not reached), respectively. One-hundred forty-eight patients were evaluated for late toxicity (follow-up >6 months): 51 (34.4%) patients had grade ≤2 fibrosis, 11 (7.4%) patients experienced grade 3 fibrosis. Two (1.3%) cases of rib fracture occurred. One case of toxic death (grade 5) has been reported. Median OS was 39 months. At the univariate analysis, lesion diameter ≤18 mm correlated significantly with a longer LPFS (p = 0.001). At the multivariate analysis, lesion diameter <18 mm was predictive for longer LPFS (p = 0.006). Also, oligometastases from primary colorectal cancer was a significant predictive factor for worse LPFS (p = 0.041) and progression-free survival (p = 0.04). Conclusions: To our knowledge, the current study represents the largest series on the use of SBRT 30 Gy single dose for lung metastases. Our results confirm the effectiveness and safety of this schedule administered in selected oligometastatic patients. Further prospective series could better validate these results.